1984
DOI: 10.1002/ajpa.1330640308
|View full text |Cite
|
Sign up to set email alerts
|

Incisor size and diet revisited: The view from a platyrrhine perspective

Abstract: Allometric relationships between incisor size and body size were determined for 26 species of New World primates. While previous studies have suggested that the incisors of Old World primates, and anthropoids in general, scale isometrically with body size, the data presented here indicate a negative allometric relationship between incisor size and body size among New World species. This negative allometry was exhibited by platyrrhines when either upper or lower incisor row length was regressed against body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 20 publications
6
52
2
Order By: Relevance
“…Previous studies of dentition dimensions and functional demands placed upon the dentition showed that primates who consume relatively hard, resistant foods tend to have larger incisors (Hylander, 1975;Eaglen, 1984;Shellis and Hiiemae, 1986) or larger molars and associated features (Kay, 1975(Kay, , 1981Kay et al, 1978). The present study found relatively larger incisors in the exudate-feeding O. crassicaudatus than in the frugivorous O. garnettii.…”
Section: Morphology Of the Anterior Dentition And Exudate-feeding In contrasting
confidence: 39%
“…Previous studies of dentition dimensions and functional demands placed upon the dentition showed that primates who consume relatively hard, resistant foods tend to have larger incisors (Hylander, 1975;Eaglen, 1984;Shellis and Hiiemae, 1986) or larger molars and associated features (Kay, 1975(Kay, , 1981Kay et al, 1978). The present study found relatively larger incisors in the exudate-feeding O. crassicaudatus than in the frugivorous O. garnettii.…”
Section: Morphology Of the Anterior Dentition And Exudate-feeding In contrasting
confidence: 39%
“…Previous attempts to estimate body mass from various skeletal and dental proxies in anthropoids have emphasized the Catarrhini (Old World ''monkeys'' and hominoids) (e.g., Delson et al, 2000), rather than platyrrhines (Hills and Wood, 1984;Conroy, 1987;Martin, 1990). Since the most reliable morphometric correlates of body mass are identified in the context of comparisons to phylogenetically closely related taxa (Eaglen, 1984;Conroy, 1987;Damuth and MacFadden, 1990;Dagosto and Terranova, 1992), we investigate these associations in platyrrhine primates.…”
Section: Introductionmentioning
confidence: 99%
“…Even incisor allometry is not well understood. Eaglen (1984) has shown that within dietary groups, Old World monkeys have larger incisors for their body size than New World monkeys.…”
mentioning
confidence: 99%